Madness in Method - some personal experiences - Vaes, Luk; Method/Art Seminar Antwerp 26.III.2024 (Antwerp Royal Conservatoire, 2024)
As a keynote, this was open access for the audience that was present. There was no publication afterwards.
FRIS
0
Keywords: HIPEX: Historical Performance Practices of Experimental Music